"Blood Sprinkled or Blood Spilt:" the History of Richard II Revisited in the Contemporary Theatre - Grzegorzewska, Małgorzata (Shakespeare in Europe, 2008)
Whereas Shakespeare's chronicles could be regarded as a characteristic expression of the ideological concerns of his own times, their contemporary theatrical reproductions constitute at best a marginal dimension of the "engaged," living theatre. Politically oriented versions of Richard III or Henry V, though important exceptions to this rule, do not change the overall impression. The question "What do Shakespeare's histories mean for us today?," together with its indispensable alternative: "What do we mean by Shakespeare (or, for that matter: by Shakespeare's history)?" still seems to elicit radically different answers from textual scholars and theatre people. The issue at stake, however, is less often the impossibility of reconciling our present concerns with those of the plays, but rather our stubborn resistance to see through the veil which some contemporary readings and/or performances draw over Shakespeare's concern with the idols of envy and violence, which we simply refuse to recognise as our idols. Therefore, we feel fully entitled to dismiss them as "our" concerns, and we conveniently place the motifs of bloody sacrifice, envious rivalry and violent revenge among the "residual," archaic, only remotely interesting aspects of Shakespearean drama.The fortunes of tragedyWe are willing to discuss Shakespeare's politics of desire, his subtle intuitions concerning the traps of theatrical representation, his political acumen. But, as René Girard has pointed out, there is more to Shakespeare's theatre than catches the eye. The French anthropologist finds in Shakespeare's plays "things hidden from the foundation of the world," as the biblical phrase goes.